PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHINGAND LEARNING (CTL)BERBANTU MEDIA GAMBARTERHADAPHASIL BELAJAR,KINERJA GURU DAN AKTIVITAS SISWA IPS SEMESTER 2 KELAS VI SDNEGERI 1 BUGO JEPARA - Singgih Adhi P; Lynda Puspita Sari (Universitas PGRI Semarang, 2015)
This research is motivated by low yields and social studies teachers do not use the model of learning in learning. The problem in this research is